Enhanced chemical vapor deposition of monolayer MoS2 films via a clean promoter - Zhang, Hongzhou; Sun, Yue; Kannan, Kaushik; Gannon, Lee; Guo, Xuyun; Rafferty, Aran; Gaff, Karl; Mullani, Navaj (My University, 2025)
Two-dimensional (2D) transition metal dichalcogenides, exemplified by molybdenum disulfide (MoS2), have shown exceptional potential for data-centered, energy-efficient electronic applications due to their unique electrical, optoelectronic, and mechanical properties. However, challenges such as the controllable synthesis of high-quality, large-area 2D MoS2 films and the mitigation of contamination during growth remain significant barriers to their integration into advanced technologies. Here, photoresist S1813 is innovatively utilized as a contamination-free growth promoter, enabling the clean and scalable synthesis of high quality 2D MoS2 on SiO2/Si substrate with desirable grain structures via chemical vapor deposition. By optimizing the reactant concentration and S/Mo ratio, enhanced MoS2 growth with improved quality is achieved, as evidenced by the increased MoS2 flake size and coverage, alongside a strong photoluminescence A exciton peak at 1.84 eV. This approach facilitates the clean and selective growth of high-quality 2D MoS2, establishing a robust pathway for the practical implementation of 2D MoS2 in next-generation electronic devices.
PUBLISHED
Keywords: Nanoscience & Materials; Applied physics; ELECTRON MICROSCOPY; Experimental Physics; Nanotechnology; Nanotechnology